2004
DOI: 10.1002/app.20117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bis(diisopropyl)thiophosphoryl disulfide on the covulcanization of styrene–butadiene rubber and ethylene–propylene–diene (monomer) blends

Abstract: Covulcanization of elastomer blends constituting styrene-butadiene rubber (SBR) and ethylene-propylene-diene (monomer) rubber (EPDM) was successfully performed in the presence of reinforcing fillers like carbon black and silica by using a multifunctional rubber additive, bis(diisopropyl)thiophosphoryl disulfide (DIPDIS). The polarity of EPDM rubber was increased by a two-stage vulcanization technique, which allowed the formation of rubberbound intermediates. In this way the migration of both curatives and rein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…To date most research into the covulcanization of dissimilar rubber blends has focused on sulfur curing systems; for example, Ghosh et al studied the effect of a multifunctional rubber additive, bis(diisopropyl)thiophosphoryl disulfide (DIPDIS) on the covulcanization of SBR/EPDM, NR/EPDM, and NBR/EPDM blend systems to restrict the curative migration into the more unsaturated rubber. As a result, the cure‐rate mismatch problem could at least be ameliorated 11–13…”
Section: Introductionmentioning
confidence: 99%
“…To date most research into the covulcanization of dissimilar rubber blends has focused on sulfur curing systems; for example, Ghosh et al studied the effect of a multifunctional rubber additive, bis(diisopropyl)thiophosphoryl disulfide (DIPDIS) on the covulcanization of SBR/EPDM, NR/EPDM, and NBR/EPDM blend systems to restrict the curative migration into the more unsaturated rubber. As a result, the cure‐rate mismatch problem could at least be ameliorated 11–13…”
Section: Introductionmentioning
confidence: 99%
“…The lowering of the torque in the filled rubber compounds is a common fact when non-reinforcing clay, calcium carbonate and silica without silane coupling agent, such as in this case, are used as fillers [25]. The influence of the different fillers on the curing parameters is quite complex.…”
Section: Resultsmentioning
confidence: 99%
“…However, unluckily and most frequently, it has been found that the obtained material from covulcanization has a reduced mechanical strength in comparison with its expected values. [2][3][4] Ethylene-propylene diene monomer (EPDM) rubber is a terpolymer of ethylene, propylene, and a small amount of a nonconjugated diene. EPDM provides excellent resistance to weather, heat, and chemicals since it has a nonpolar structure and saturated main chain.…”
Section: Introductionmentioning
confidence: 99%
“…In order to transfer different features to a polymeric system, blending two or more rubbers can be carried out by covulcanization. However, unluckily and most frequently, it has been found that the obtained material from covulcanization has a reduced mechanical strength in comparison with its expected values 2–4 …”
Section: Introductionmentioning
confidence: 99%